Historical legacies and current challenges for the future resilience of the farming system in the Altmark - Franziska Appel; Anneke Meier; Franziska Ollendorf (Resilient and sustainable farming systems in Europe: Exploring diversity and pathways, 2022)
Up to the present, the farming system in the Altmark is shaped by its historical legacies of a socialist economy which together with contemporary challenges impact its functions and resilience capacities. Based on the analysis of this interplay, the chapter discusses possible future strategies to enhance the resilience of the farming system in the Altmark.
Keywords: 330